Setting standards and primary school teachers’ experiences of the process - Scherman, Vanessa; Zimmerman, Lisa; Howie, Sarah J.; Bosker, Roel (Faculty of Education, University of the Free State, 2014)
In South Africa, very few standard-setting exercises are carried out in education and, if they are, teachers are not involved in their execution. As a result, there is no clear understanding of what the standard is and how it was arrived at. This situation is compounded when teachers are held accountable when learners do not meet the prescribed standards. The aim of this paper is to explore how teachers experienced a standard-setting process and if any reflection on teaching and learning practices took place. The research question addressed is: How was the SAMP standard-setting exercise experienced by teachers? Standard setting is an important component in monitoring systems whether national or school-based monitoring systems. The South African Monitoring system for Primary Schools (SAMP) is a school-based monitoring system. The Grade 1 SAMP assessment is administered in English, Afrikaans and Sepedi. As part of SAMP, a standard-setting exercise was undertaken for the Grade 1 assessment to better inform the dissemination of performance results to schools. As part of a bigger research project, a participatory qualitative approach was followed in which 27 participants were asked to partake in a modified Interactive Qualitative Analysis (IQA) process. Several themes were identified by the teachers, namely reflections on practice; emotions before and during the standard setting workshop; benefits of working in a group; and improvements in the process. In this article, these themes are explored and their relevance for standard setting within school contexts discussed.
Keywords: Standard setting; Monitoring; Professional development; Standard-setting approaches; South African primary schools; South African Monitoring and Feedback System for Primary Schools; SAMP